Movement economy in breaststroke swimming: A survival perspective - Stallman, R. K.; Major, J.; Hemmer, S.; Haavaag, G. (Biomechanics and Medicine in Swimming XI, 2010)
When adopting a head up position in breaststroke the center of gravity is displaced backward, farther from the center of buoyancy. This causes a tendency for the legs to sink, increasing the angle of the body with the horizontal plane and concurrently, resistance. Increased resistance theoretically reduces survival possibilities. The purpose of this study was to quantify the difference in energy expenditure for breaststroke with the head held constantly above the surface and for breaststroke performed with normal breathing. Classic Douglas bag respirometry was used. During submaximal swimming, the volume of oxygen uptake was significantly higher when swimming with the face constantly above the surface than with normal breathing. Both pulse rate and blood lactate levels were also significantly higher when swimming "head up".